Quantum well states and amplified spin-dependent Friedel oscillations in thin films - Bouhassoune, Mohammed; Zimmermann, Bernd; Mavropoulos, Phivos; Wortmann, Daniel; Dederichs, Peter H.; Blügel, Stefan; Lounis, Samir (NATURE COMMUNICATIONS, 2014)
Electrons mediate many of the interactions between atoms in a solid. Their propagation in a material determines its thermal, electrical, optical, magnetic and transport properties. Therefore, the constant energy contours characterizing the electrons, in particular the Fermi surface, have a prime impact on the behaviour of materials. If anisotropic, the contours induce strong directional dependence at the nanoscale in the Friedel oscillations surrounding impurities. Here we report on giant anisotropic charge density oscillations focused along specific directions with strong spin-filtering after scattering at an oxygen impurity embedded in the surface of a ferromagnetic thin film of Fe grown on W(001). Utilizing density functional theory, we demonstrate that by changing the thickness of the Fe films, we control quantum well states confined to two dimensions that manifest as multiple flat energy contours, impinging and tuning the strength of the induced charge oscillations which allow to detect the oxygen impurity at large distances (approximate to 50 nm).